The Exoticism of Olivier Messiaen - Rucsanda, Mădălina Dana; Karácsony, Noémi (Babes-Bolyai University Cluj-Napoca, 2023)
In the final decades of the 19th century and in the 20th century, exoticism and orientalism contributed greatly to the evolution and innovation of Western music composition. Using the rules and techniques of Western music, composers incorporated in their works elements pertaining to or inspired by foreign cultures and their music. The current study continues the investigations brought to attention by the authors in their previous articles: it desires to reveal and analyze the way exoticism and orientalism influenced the creation of various composers, pointing to those aspects that represented innovation brought about by the contact with the music and culture of other cultures than the Western world. The musical language of Messiaen is deeply rooted in the universal musical heritage, comprising elements belonging to the music of the Ancient Greeks, the Orient, Africa, or Europe. The present paper presents and offers examples regarding the way rhythm and melody are organized and employed by Messiaen using means that are inspired by Hindu music: the correspondence between the deçî-tâlas (Hindu rhythms) and Messiaen’s use of rhythm, as well as the similarities between the Hindu rāga and the modes of limited transposition. Apart from the Hindu influences on rhythm and melody, Messiaen was also inspired by the Japanese Gagaku, its instruments, and relation between harmony and melody, as well as Indonesian music (Balinese and Javanese), both having an important influence on the way the composer perceives and creates timbre. But apart from striving to create new means of musical expression using exotic elements, Messiaen desired to unveil certain spiritual and theological truths, mirrored in his music and the construction of his musical discourse.
Keywords: exoticism; Hindu; Japanese; Bali; Messiaen